Analysis of lethal and sublethal doses: Comparative toxicity of three commonly used pesticides on Blattella germanica, an important allergen and vector of pathogens - Mozaffar Vahedi; Kourosh Azizi; Amin Hosseinpour; Abbasali Raz; Hadi Aligholi; Mohammad Hoseini; Aboozar Soltani (Heliyon)
The study investigates the comparative toxicity of three widely used insecticides-fenitrothion, malathion, and deltamethrin-on Blattella germanica, a major urban pest.Using bioassay tests based on World Health Organization (WHO) protocols, we determined the lethal doses 50 (LD50) for each insecticide. 2.5 mL of each insecticide in acetone was placed in glass jars. Ten adult male cockroaches were tested per dilution, with three to four replicates. Acetone alone served as the control. After 1 h of exposure, the cockroaches were moved to containers with food and water, and mortality was recorded after 72 h. Probit regression analysis was employed to analyze the mortality rates at various doses, and statistical significance was confirmed for all tested insecticides.Results showed that malathion had the lowest lethal dose, with an LD50 of 4.29 ppm, making it more potent at lower concentrations. Fenitrothion followed with an LD50 of 5.11 ppm, while deltamethrin exhibited the highest LD50 of 8.56 ppm, indicating lower toxicity at standard concentrations.The study also emphasized the importance of understanding sublethal doses, which, though not immediately fatal, could induce behavioral and physiological changes leading to pesticide resistance. The findings provide critical insights for pest management strategies, highlighting the need for appropriate dosing to balance efficacy with safety concerns. This research establishes baseline data for future studies on B. germanica and its resistance mechanisms, contributing to improved pest control measures with minimal environmental impact.